Development Of Village Economic Potentials Through Village-Owned Businesses (Bumdes) To Increase Community Well-Being Community Welfare In The Village Nanjung Bandung District - Rira Nuradhawati; Yovinus Yovinus; Muhammad Aldi (Universitas Pancasakti Tegal, 2024)
Villages should receive serious attention from the central government with the birth of policies related to economic empowerment that are carried out by gathering and institutionalizing community economic activities. According to qualitative methods are research to describe and analyze phenomena, events, beliefs, attitudes, and social activities individually and in groups. Qualitative methods are a collection of methods to analyze and understand more deeply the meaning of several individuals and groups considered as humanitarian problems or social problems community participation in the implementation of business in BUMDes Nanjung is still not optimal, it can be seen that the stigma from the community towards the presence of BUMDes is still not in accordance with expectations of potential development in BUMDes itself. This is certainly one of the problems and challenges for BUMDes Nanjung. By understanding the causes of low community participationthe type of business at BUMDES Mandiri Sejahtera Nanjung has been carried out well, this can be seen that the implementation of the type of business carried out at BUMDes Nanjung utilizes the potential of Human Resources and other equipment that tends to be economical and utilization in the creative field can be a very good innovation Management of business sustainability in BUMDes, in this case management is said to be lacking because it is still limited and too early in the management of BUMDes Nanjung which leaves some shortcomings in carrying out business through BUMDes Nanjung.